POSSIBILITIES OF CREATING TOURIST AND RECREATIONAL COMPLEXES BASED ON THE LANDSCAPE CONDITIONS OF THE MOUNTAINOUS DISTRICTS OF THE ALMATY REGION, KAZAKHSTAN - Bayan S. KERIMBAY; Kuat M. BAIMYRZAEV; Nurzhan N. KERIMBAY; Zaure K. KALIASKAROVA (Geo Journal of Tourism and Geosites)
The Almaty region, which is rich in natural landscapes, was established again in 2022. In this regard, the importance of regional spatial planning is taking on new forms. Considering the unique landscape potential, this project aims to create a framework for developing tourist and recreational complexes in the Uygur, Kegen, and Raiymbek regions. Creating a landscape diversity database to classify recreational resources; developing a typology for tourist and recreational complexes, considering the landscape's features and the tourism specializations. The research methods used in this study include field observations and landscape descriptions provided by the authors. A classification method has been developed to divide recreational resources into groups and sub-groups, determining their locations. The process of the developed typology is based on examples of specific types of tourist and recreational activities, as well as existing and potential tourist areas in the Almaty region and the Republic of Kazakhstan. The theoretical and methodological basis for the proposed classification and typology is based on the work of various authors and materials from the National Science Foundation of Kazakhstan. Issues of the possibilities of agricultural enterprises to provide tourists with local, natural food products have been analy zed. Based on these factors, recommendations were formulated for further developing promising tourist and recreational complexes in these areas. All authors have read and agreed to the published version of the manuscript.